Origin and quantitative source assessment of deep oils in the Tazhong Uplift, Tarim Basin. (January 2015) - Li, Sumei; Amrani, Alon; Pang, Xiongqi; Yang, Haijun; Said-Ahmad, Ward; Zhang, Baoshou; Pang, Qiuju
Highlights: Cambrian ( ) oil from ZS1, ZS1C wells was sourced from O2+3 and rocks respectively. The proportion for the deep oil from the and O2+3 rocks is about 57:43. The compound specific sulfur isotope could indicate TSR extent of the deep oil. Lower Cambrian oil was suggested to be responsible for the unusually high DBTs. Maturity impact on correlative index cannot cause reversed oil–source result. Abstract: A large amount of deep oil has been discovered in the Tazhong Uplift, Tarim Basin whereas the oil source is still controversial. An integrated geochemical approach was utilized to unravel the characteristics, origin and alteration of the deep oils. This study showed that the Lower Cambrian oil from well ZS1C ( 1x ) was featured by small or trace amounts of biomarkers, unusually high concentration of dibenzothiophenes (DBTs), high δ 34 S of DBTs and high δ 13 C value of n -alkanes. These suggest a close genetic relationship with the Cambrian source rocks and TSR alteration. On the contrary, the Middle Cambrian oils from well ZS1 ( 2a ) were characterized by low δ 13 C of n -alkanes and relatively high δ 34 S of individual sulfur compounds and a general "V" shape of steranes, indicating a good genetic affinity with the Middle–Upper Ordovician source rocks. The middle Cambrian salt rock separating the oils was suggested to be one of the factors responsible for the differentiation. It was suggested that most of the deep oils in the Tazhong Uplift were mixed source based on biomarkers and carbon isotope, which contain TSR altered oil in varied degree. The percentage of the oils contributed by the Cambrian–Lower Ordovician was in the range of 19–100% (average 57%) controlled by several geological and geochemical events. Significant variations in the δ 34 S values for individual compounds in the oils were observed suggesting a combination of different extent of TSR and thermal maturation alterations. The unusually high DBTs concentrations in the Tazhong-4 oilfield suggested as a result of mixing with the ZS1C oil ( 1x ) and Lower Ordovician oils based on δ 34 S values of DBT. This study will enhance our understanding of both deep and shallow oil sources in the Tazhong Uplift and clarify the formation mechanisms of the unusually high DBTs oils in the region.